If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1wy = mfory Reorder the terms: -1wy + y = mfory Solving -1wy + y = fmory Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1y' to each side of the equation. -1wy + y + -1y = fmory + -1y Combine like terms: y + -1y = 0 -1wy + 0 = fmory + -1y -1wy = fmory + -1y Divide each side by '-1y'. w = -1fmor + 1 Simplifying w = -1fmor + 1 Reorder the terms: w = 1 + -1fmor
| 3u+3=6(u-1) | | x^5+3x^4-10x^3-30x^2+16x+48=0 | | -(5x-11)+3(6X+5)= | | -3(v-5)=-7v+7 | | 2X^2+3Y^2=10 | | 9x+11=5x+43 | | 6F+2+3F+10+F+5= | | 2w+4x+12y+7w+10x-4w=Equation | | 0.8=3 | | 1x=2x+2 | | -3(5p+5)-2(6-11p)=3(2+2p) | | a^2-32=-4a | | 12.75b=4 | | 90+112+73+x=360 | | 24y-22=-(1-6y) | | 8.2+x=23.4 | | -9(x-2)=8(x-3) | | 2x^2-38+180=0 | | F=(L-3)200 | | 9-x-x+8=0 | | -x+6=2x+18 | | 24=-(x-8) | | 2w+4x+12y+7w+10x-4w= | | 3m(7-21m)=0 | | 7x-y+49=0 | | 5(x+5)+5=5(x-8) | | 6x+8=4x-8 | | -22x-114-3x=-44x | | 9/2+49/4+7/2+3/4= | | -7(w-2)=5(3-3) | | -0.8(w-8)=0.4(3w-9) | | 4(x+4)-8x=4 |